Wideband Substrate Integrated Cavity-Backed Dielectric Resonator Antenna at Sub-6-GHz Band - Reza Shamsaee Malfajani; Jean-Jacques Laurin; Mohammad S. Sharawi (IEEE Open Journal of Antennas and Propagation)
The design and implementation of a wideband single-mode dielectric resonator antenna (DRA) with a substrate integrated cavity-backed structure is presented in this paper. Two short-circuited striplines with differential feeding are placed inside the substrate integrated cavity (SIC) for pure mode excitation of the DRA, providing stable radiation characteristics, and low cross polarization levels. The cavity is coupled to the cylindrical DRA through an annular slot. The fundamental ${ HEM}_{11δ }$ mode of the DRA is excited over a wide frequency band, as a result of the similar field distribution created on the coupling annular slot by two modes inside the cavity. Measurement results show a maximum gain of 8.2 dBi at 5.45 GHz. The gain is 7.8 dBi at the center frequency of 5.15 GHz and its 1-dB bandwidth is 23%. The measured 10-dB return loss bandwidth is 26% (centered at 5.15 GHz) which is the highest among the previously reported works based on cavity-backed DRAs and single-mode excited DRAs. The measured co-polarization and cross-polarization gain difference at the boresight direction is more than 26 dB. This antenna element can be used to cover a wide range of wireless standards in wireless access point and applications due to its stable wide band performance.